2021
DOI: 10.1089/crispr.2020.0115
|View full text |Cite
|
Sign up to set email alerts
|

Genome Editing Using the CRISPR-Cas9 System to Generate a Solid-Red Germline of Nile Tilapia (Oreochromis niloticus)

Abstract: In recent years, there has been increasing demand for red tilapia, which are commercial strains of hybrids of different tilapiine species or red variants of highly inbred Nile tilapia. However, red tilapia phenotypes are genetically unstable and affected by environmental factors, resulting in nonuniform coloration with black or dark-red color blotches that reduce their market value. Solute carrier family 45 member 2 (SLC45A2) is a membrane transporter that mediates melanin biosynthesis and is evolutionarily co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 94 publications
0
17
0
1
Order By: Relevance
“…A recent study describes the generation of stable and heritable red tilapia phenotype through induced loss-of-function mutations in the slc45a2 gene of Nile tilapia ( Oreochromis niloticus ) [ 102 ]. The solute carrier family 45 member 2 ( slc45a2 ) is a membrane-associated transporter protein that mediates melanin biosynthesis and is evolutionarily conserved from fish to humans.…”
Section: Gene Editing In Fish Farm Species Using Crispr/cas9 and Othe...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study describes the generation of stable and heritable red tilapia phenotype through induced loss-of-function mutations in the slc45a2 gene of Nile tilapia ( Oreochromis niloticus ) [ 102 ]. The solute carrier family 45 member 2 ( slc45a2 ) is a membrane-associated transporter protein that mediates melanin biosynthesis and is evolutionarily conserved from fish to humans.…”
Section: Gene Editing In Fish Farm Species Using Crispr/cas9 and Othe...mentioning
confidence: 99%
“…( C ) shows slc45a2 -RNPs-injected mutant fish with 97–99% loss of melanin in the skin and no melanin in the eye. ( D ) shows post sexual maturation, F0 mutant displaying a complete loss of melanin [ 102 ].…”
Section: Figurementioning
confidence: 99%
“…Because the Tyrosine gene play a role in catalyzed the melanin biosynthesis in pigment cells and also determined vertebrate coloration. In Nile Tilapia (Oreochromis niloticus) [32], the slc45a2 gene was knocked out, which mediated melanin biosynthesis and produced an albino variant with red skin and eyes. In Chinese lamprey (Lethenteron morii) [45], the slc45a5 gene was knocked out, which resulted in the 'Golden phenotype' of the fish.…”
Section: Pigmentationmentioning
confidence: 99%
“…The DSB can be repaired by two major DNA repair pathways, namely, nonhomologous end joining (NHEJ) and homology-directed repair (HDR). The NHEJ pathway repairs two adjacent strands of DNA that are error-prone and usually induce unpredictable insertion or deletions (indels) and substitutions (Segev-Hadar et al, 2021). Additionally, if a repair template is present, another pathway HDR can be used to insert the desired mutations for precise gene editing (Figure 1).…”
Section: What Is Crispr and How Does It Work?mentioning
confidence: 99%
“…Recently, there is an increasing market demand for red tilapia that are the hybrids of different tilapia species or the red variant of the highly inbred Nile tilapia, and this red-color phenotype is unstable, resulting in a nonuniform coloration in appearance or dark-red color blotches that reduce the market value. Hence, the CRISPR/Cas9 system was used to target the slc45a2 gene in melanin biosynthesis and produces an albino variant of Nile tilapia with red skin and eyes (Segev-Hadar et al, 2021). Additionally, researchers are utilizing slc family genes to improve the visual confirmation of knockout fish or strain, and in such a research, Pandey et al (2021) showed that slc2415 mutants showed reduced melanin pigmentation in the retina and bodies of Kawakawa (Euthynus affinis), highlighting toward a future where the visual recognition of a genome-edited stock will be possible.…”
Section: Pigmentationmentioning
confidence: 99%